Comparative Studies of Different Switching Patterns for Direct and Indirect Space Vector Modulated Matrix Converter. (30th December 2012) - Shabanpour, Amin; Gholami, Sasan; Seifi, Ali Reza
Abstract : This paper presents a MATLAB/Simulink simulation of direct and indirect space vector modulation for matrix converter. Different switching patterns for both direct and indirect methods are simulated and compared. Three criteria are chosen to compare the performance of switching patterns: (1) total harmonic distortion (THD); (2) harmonic spectrum analysis of output voltages; and (3) number of switching in each switching period. Switching strategies are completely implemented using the power library in MATLAB/Simulink environment.